Social networks in the current process of the reconstruction of San Gregorio Atlapulco, Xochimilco, México City (REVISTA NODO, 2019)
This paper discusses the main socio-environmental elements that influence the presence of natural and anthropogenic risks, as well as the vulnerability of different geographical areas and social groups of this city, which has been affected repeatedly throughout history by earthquakes and floods. An assessment is given of the deleterious effects resulting from the 1985 and 2017 earthquakes. The main problems are identified, especially as related to housing loss and the processes of depletion and contamination of water bodies that supply the inhabitants of Mexico City. The various forms of participation by public and social institutions are identified as they occurred in the stages of emergency response and reconstruction of affected areas of the city. The objective of this article is to recount the process of construction of social networks to support victims in Mexico City, in particular in the town of San Gregorio Atlapulco, Xochimilco. Aspects examined include participation by the public sector, taking into account the planning tools and public policies of the current government; the contribution of the private sector, ranging from covering basic needs to constructing housing; and the participation of existing social organizations and new organizations that arose in response to the earthquake, in which the work done by young people is particularly notable. In addition, the paper gives a comparative analysis of the effects of the September 1985 and 2018 earthquakes, showing the advances in resource management capacity, specifically of social organizations; and advances in technological, scientific and economic knowledge supporting the reconstruction process in the affected areas in response to emergencies, with particular reference to Mexico City. Among the problems identified there exists a deficiency in updating and application of environmental conservation and urban development programs associated with social vulnerability, and a deficiency in communication with the victims, especially in respect to clarity about the spending of funds allocated to reconstruction.
Keywords: Environment; Risks and vulnerability; Social organization; Public policy